Discovery of Small Molecule KCC2 Potentiators Which Attenuate In Vitro Seizure-Like Activity in Cultured Neurons - Prael III, Francis J.; Kim, Kwangho; Du, Yu; Spitznagel, Brittany D.; Sulikowski, Gary A.; Delpire, Eric; Weaver, C. David (Frontiers in Cell and Developmental Biology, 2022)
KCC2 is a K+-Cl- cotransporter that is expressed in neurons throughout the central nervous system. Deficits in KCC2 activity have been implicated in a variety of neurological disorders, including epilepsy, chronic pain, autism spectrum disorders, and Rett syndrome. Therefore, it has been hypothesized that pharmacological potentiation of KCC2 activity could provide a treatment for these disorders. To evaluate the therapeutic potential of pharmacological KCC2 potentiation, drug like, selective KCC2 potentiators are required. Unfortunately, the lack of such tools has greatly hampered the investigation of the KCC2 potentiation hypothesis. Herein, we describe the discovery and characterization of a new class of small-molecule KCC2 potentiator. This newly discovered class exhibits KCC2-dependent activity and a unique mechanistic profile relative to previously reported small molecules. Furthermore, we demonstrate that KCC2 potentiation by this new class of KCC2 potentiator attenuates seizure-like activity in neuronal-glial co-cultures. Together, our results provide evidence that pharmacological KCC2 potentiation, by itself, is sufficient to attenuate neuronal excitability in an in vitro model that is sensitive to anti-epileptic drugs. Our findings and chemical tools are important for evaluating the promise of KCC2 as a therapeutic target and could lay a foundation for the development of KCC2-directed therapeutics for multiple neurological disorders.